Effects of aerobic exercise on executive function among overweight and obese children: a systematic review and meta-analysis - Wang, Yi; Wang, Hao; Zhao, Hongpeng (Frontiers in Psychology, 2024)
Objective: Overweight and obesity are serious public health issues worldwide and significantly impair children's executive function (EF). However, there is no consensus regarding the benefits of aerobic exercise, on the EF of overweight and obese children. This study systematically evaluated the intervention effects of aerobic exercise on EF and its subcomponents (inhibitory control, working memory, and cognitive flexibility) in overweight and obese children. Methods: We searched six databases-PubMed, Web of Science, Cochrane Library, Embase, EBSCOhost, and China National Knowledge Infrastructure-until March 17, 2024 for randomized controlled trials examining the effects of aerobic exercise on the EF of overweight and obese children the Cochrane Risk of Bias Assessment Tool. Following heterogeneity testing, RevMan 5.4 and Stata 17.0 were used for metaanalysis and subgroup analysis of the three indicators. The standardized mean difference (SMD) and 95% confidence intervals (CI) were used as statistical measures for effect analysis with the SMD value as the effect size and a P-value of ≤0.05 indicating statistical significance. Results: Eighteen studies involving 1,260 participants were included. Aerobic exercise significantly improved overall EF (SMD = -0.50, 95% CI [-0.68, -0.32], P < 0.01) with a moderate to high positive effect on inhibitory control (SMD = -0.52, 95% CI [-0.72, -0.31], P < 0.01) and working memory (SMD = -0.63, 95% CI [-1.06, -0.20], P < 0.01) but not on cognitive flexibility (SMD = -0.32, 95% CI [-0.71, 0.07], P = 0.11). These results suggest that EF in overweight and obese children is influenced by factors such as exercise characteristics and body mass index (BMI). Subgroup analysis revealed a significant moderating effect of exercise type, exercise intensity, session time, and individual BMI on EF. Conclusion: Aerobic exercise selectively improved EF in overweight and obese children. Subgroup analysis indicated that cognitive engagement in ball game interventions of at least moderate intensity and a single session of 25-40 min are more beneficial for improving EF in overweight and obese children. Extremely obese children (BMI > 25 kg/m 2 ) do not benefit from the intervention, highlighting the need for a specific focus on intervention outcomes in future studies.